'I am studying in the US but': observations and insights from Caribbean college students. (2nd January 2017) - Bailey, Erold K.
ABSTRACT: This paper examines the experiences and views of 12 Caribbean students studying at four Liberal Arts colleges and one large university in the Northeast, USA. The purpose of the study was to ascertain how young educated potential immigrants to the US today are thinking about race, identity, and homeland. The data were gathered through a 12-item open-ended questionnaire electronically administered through Google Forms . Among other issues, the researcher wanted to learn about participants': decision to study in the US, experiences with race, identity and attitudinal shifts, feelings about being assigned racial labels, and current thinking about returning to their home countries. The findings highlight the acceptance of racial labels except for 'African American', a dogged adherence to national identity, the challenge of adjusting to the US racialized space, the view of the US as an education and economic transitional point for migrants on their return journey to their home countries, the formulation of new understandings and attitudes regarding mixed ancestry, and the defining role of sexual orientation in the attitude towards home country versus the US.